Nutritional Education Using Edutaiment Methods to Improve Clean and Healthy Living Behavior During the Covid-19 Pandemic - Aritonang, Evawany Yunita; Siagian, Albiner (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The COVID-19 pandemic has an impact on clean and healthy living behaviors. This affects the improvement of clean living behavior and healthy behavior in a balanced manner so as to prevent exposure to covid-19. The purpose of this service is to increase students' knowledge, attitudes and behavior about PHBS and washing hands using soap with running water, which is used in this service, namely the edutaiment method. The educational method was carried out directly with edutainment to students of Muhammadyah 03 Junior High School for 30 minutes. To assess the success of education, pretests and post tests were conducted. The results of 19 students of SMP Muhammadyah 3 Medan Selayang, Medan City. The number of student participants who took part in the pretest and post test obtained a value for the pretest in the good category of 10.5% while in the moderate category of 89.5% and the value obtained by the post test in the good category 94.7% while in the moderate category 5.3%. The change in value in the good category increased by 85.2% and in the moderate category decreased by 84.2%. The interest of students to implement hand washing is very large, so that the counseling is easily accepted and can create a positive attitude towards the message conveyed which affects the behavior of students.